Non-linear control for enhanced solar power under partial shading and AC load variations - Sabri Khadija; El Maguiri Ouadia; Farchi Abdelmajid (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
This paper solves the control problem to track the maximum power in grid-connected PV systems to catch up with the changes and meet the energy demand, given the irregular and arbitrary nature of the solar source. Our work addresses the following objectives: i) extracting the maximum available power under partial shading, ii) and having a unit power factor. To achieve the above objectives, we have integrated two control components. The first one is dedicated to the extraction of the maximum power point (MPPT) particle swarming algorithm (PSO) with a backstepping controller, by shaking on the DC/DC converter duty cycle to increase the robustness and stability of the system. The backstepping control of the three-phase voltage source inverter is the second part. To verify the effectiveness of the introduced system, modelling and simulation are verified in MATLAB/Simulink.